Thermal stability of alkanethiolate and aromatic thiolate self-assembled monolayers on Au(111): an X-ray photoelectron spectroscopy study - Asyuda, Andika; Das, Saunak; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2021)
Applications of functional self-assembled monolayers (SAMs) rely to a large extent on their stability, with the thermal stability being of particular importance. In this context, thermal stability of archetypical, non-substituted alkanethiolate (AT) and aromatic thiolate (ArT) SAMs on gold was studied by synchrotron-based high-resolution X-ray photoelectron spectroscopy, taking several monolayers with different lengths of the molecular backbones as representative examples and heating them in UHV. Evaporated, grain-structured Au(111) was used as the support, in view of broad practical relevance of this substrate type. AT and ArT SAMs were found to be stable up to temperatures of ∼373 and ∼383-393 K, respectively, followed by extensive molecular desorption and decomposition upon further heating. The decomposition was mediated by the cleavage of C-S bonds, which represented the so-called “weak or weakest link” in the systems. This process contributed minorly to the temperature-induced degradation of AT SAMs but was the dominant degradation channel for the ArT case. The residual films exhibited ∼10% (AT) or ∼ 35% (ArT) of the initial packing density and represented a superposition of the laying-down phase and atomically adsorbed sulfur, with a possible coexistence of a restructured, standing-up phase in the ArT case.